THE WORLD OF THE THING IN BOHDAN TOMENCHUK’S POETRY (ON THE BASE OF BOOK ‘THE CITY OF HEROES AND WITNESS) - Деркачова, О. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with status of thing in Bohdan Tomenchuk’s poetry on the base of aspects: lyric hero – thing, artistic time – thing, artistic space – thing. Frequency of using some names of things is determined. It also analyzed the role of thing in text interpretation. (Non)thing world has got two levels: the world without things and the world with things. The hero exists in both of them.